2014
DOI: 10.1063/1.4891446
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric steady streaming as a mechanism for acoustic propulsion of rigid bodies

Abstract: Recent experiments showed that standing acoustic waves could be exploited to induce selfpropulsion of rigid metallic particles in the direction perpendicular to the acoustic wave. We propose in this paper a physical mechanism for these observations based on the interplay between inertial forces in the fluid and the geometrical asymmetry of the particle shape. We consider an axisymmetric rigid near-sphere oscillating in a quiescent fluid along a direction perpendicular to its symmetry axis. The kinematics of os… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
187
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(194 citation statements)
references
References 36 publications
7
187
0
Order By: Relevance
“…The propulsion mechanism of metallic microrods in standing ultrasonic waves was recently examined more closely from a theoretical perspective by Nadal and Lauga . They proposed a new theory based on asymmetric local streaming, and provided a rigid theoretical framework to describe the process by which the small amplitude oscillation of rigid bodies in a standing wave can translate, via shape asymmetry‐induced local acoustic streaming effects, into motion in a direction perpendicular to the acoustic wave.…”
Section: Acoustic Propulsionmentioning
confidence: 88%
See 2 more Smart Citations
“…The propulsion mechanism of metallic microrods in standing ultrasonic waves was recently examined more closely from a theoretical perspective by Nadal and Lauga . They proposed a new theory based on asymmetric local streaming, and provided a rigid theoretical framework to describe the process by which the small amplitude oscillation of rigid bodies in a standing wave can translate, via shape asymmetry‐induced local acoustic streaming effects, into motion in a direction perpendicular to the acoustic wave.…”
Section: Acoustic Propulsionmentioning
confidence: 88%
“…Based on their calculation, a roughly spherical particle with an aspect ratio of 10 in a standing acoustic wave could be propelled at ≈26 μm s −1 in conditions similar to those used by a previous group . Although this value is one order of magnitude smaller than the experimentally measured particle speed (up to 200 μm s −1 ), the theoretical framework established by Nadal and Lauga has laid the foundation for a more coherent and accurate theory.…”
Section: Acoustic Propulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other forms of motion driven by self-generated gradients have more recently been demonstrated. For example, motors driven by self-diffusiophoresis (Figure 2b) are propelled by self-generated chemical concentration gradients (60,(76)(77)(78), and self-acoustophoretic motors (Figure 2c) are propelled by asymmetric steady streaming of the fluid around them in an acoustic field (63,(79)(80)(81). Temperature gradients can also be used by microparticles to create motion, a mechanism referred to as self-thermophoresis (65)(66)(67).…”
Section: Development Of Nano-and Micromotorsmentioning
confidence: 98%
“…In the former, the double energy transduction increases the system's complexity and dramatically reduces its efficiency, making this method not suitable for small-scale devices. An example of the second approach is the use of geometrically asymmetric particles and inertial forces in fluids to generate steady stress on the particles, resulting in a finite propulsion speed, which was recently modeled by Lauga et al 12 and experimentally demonstrated by Mallouk et al 13,14 and Wang et al 15,16 A way to increase efficiency, while also enabling control of multiple DoFs, is to exploit acoustic resonances 17 and frequency-division multiplexing. A spherical gas bubble submerged in a liquid, for instance, has a resonant frequency as described by the Rayleigh-Plesset equation, 18 at which large volume oscillation is observed, and fluid streaming away from the bubble is induced.…”
mentioning
confidence: 99%